2015
DOI: 10.4049/jimmunol.1402419
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12 Regulates through JAK1 and JAK2 Formation of Productive Immunological Synapses

Abstract: The adaptive immune response requires interaction between T cells and APC to form a specialized structure termed the immune synapse (IS). Although the TCR is essential for IS organization, other factors such as chemokines participate in this process. In this study, we show that the chemokine CXCL12-mediated signaling contributes to correct IS organization and therefore influences T cell activation. CXCR4 downregulation or blockade on T cells caused defective actin polymerization at the contact site with APC, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…Moreover, localization of CCR5 and CXCR4 at the IS and exposure to their ligands presented by APCs might desensitize the chemokine receptor signal and stabilize the contact site . In line with this, interfering with G protein‐dependent CXCR4 and JAK1/2 signaling correlated with reduced actin polymerization at the contact site, altered structure of the IS, and mislocalization of the microtubule‐organizing center …”
Section: Chemokine Receptors As Co‐stimulatory Molecules For Efficienmentioning
confidence: 69%
See 2 more Smart Citations
“…Moreover, localization of CCR5 and CXCR4 at the IS and exposure to their ligands presented by APCs might desensitize the chemokine receptor signal and stabilize the contact site . In line with this, interfering with G protein‐dependent CXCR4 and JAK1/2 signaling correlated with reduced actin polymerization at the contact site, altered structure of the IS, and mislocalization of the microtubule‐organizing center …”
Section: Chemokine Receptors As Co‐stimulatory Molecules For Efficienmentioning
confidence: 69%
“…Distinct co-stimulatory activities have been attributed to the chemokines CCL5, CCL19, CCL21, and CXCL12. [90][91][92][93][94][95][96][97] T cell costimulation via TCR and CXCR4 was shown to enhance the expression of the activation markers CD69, CD25, and CD154 to increase T cell proliferation, as well as to augment the production of the cytokines IL-2, IFN-, IL-4, and IL-10. 90-92 CXCR4-driven IL-10 and IL-2 secretion was further noted to enhance activation of the transcription factor AP-1.…”
Section: Chemokine Receptors As Co-stimulatory Molecules For Efficienmentioning
confidence: 99%
See 1 more Smart Citation
“…Although T cells express both CXCR4 and CCR7, CCR7/CXCR4 heterodimers are not detected on these cells during immunological synapse formation. Interestingly, CXCR4 is recruited to the peripheral SMAC whereas CCR7 is not . The use of different cell types, distinct technical approaches.…”
Section: Chemokine Receptor Dimerization/oligomerization: a Potentialmentioning
confidence: 99%
“…β2M is an established prognostic factor in CLL, and reduction in β2M levels is associated with prolonged progression-free survival. 29 Recent studies demonstrated that activation of JAK and its downstream signal transducer and activator of transcription (STAT) pathway affects the levels of CXCL12/CXCR4 30 , 31 and CCL2 chemokines 32 . Treatment with ruxolitinib suppressed the expression of several chemokine and cytokines, suggesting that gene expression in CLL cells mobilized from their microenvironment 33 is different from that of steady state circulating CLL cells.…”
Section: Discussionmentioning
confidence: 99%